PENGARUH BEBAN PAJAK TANGGUHAN DAN AKRUAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Jaka, Yosep (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
ABSTRACTEarnings management is an effort of company managers to intervene or influence information in financial statements with the aim of tricking stakeholders who want to know the performance and condition of the company (Sulistyanto, 2008). This study aims to examine and determine the effect of deferred tax expenses and accruals on corporate earnings management practicesThe sample used in this study was a mining company listed on the Indonesia Stock Exchange (IDX) during the 2016-2018 period. Total mining companies listed on the IDX in 2019 were 41 companies and the total sample used was 21 companies selected using purposive sampling techniques. Data analysis methods in this study used descriptive statistical tests, classic assumption tests, multiple linear regression and hypothesis testing.The results of the research partially indicate that deferred tax expense does not significantly influence the earnings management while the accrual variable significantly influences the earnings management. But the results of the study simultaneously show that the deferred tax expense and accruals significantly influence the earnings management.Keywords: Deferred Tax Expenses, Accruals, Earnings ManagementReferensi Â Agoes, Sukrisno dan Estralita Trisnawati. (2013). Akuntansi Pepajakan edisi 3. Jakarta: Salemba Empat.Agus, Sartono. (2008). Manajemen Keuangan Teori dan Aplikasi Edisi Empat. Â Yogyakarta: BPFEAnthony, Robert N. and Vijay Govindarajan. (1995). Management Control System. Irwin : Homewood, lllinios,Bursa Efek Indonesia. 2019. Laporan Keuangan dan Tahunan. https://www.idx.co.id/perusahaan-tercatat/laporan-keuangan-dan-tahunan/. (10 Juli 2019).Dechow,P.M., R.G. Sloan. and A.P. Sweeney. (1994). â€œDetecting Earning Â Managementâ€. The Accounting Review. Vol 70. pp 193-225.Fahmi, Irham. (2013). Analisis Laporan Keuangan, Cetakan ketiga. Bandung: Â Alfabeta.Ghozali, Imam. (2005). Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, Imam. (2013). Aplikasi Analisis Multivariat dengan Program IBM SPSS. Edisi 7. Semarang: Penerbit Universitas Diponegoro.Hanlon,M. (2005). The Persistence and Pricing o fEarnings, Accruals,and Cash Flow When Firms Have Large Book-tax Differences. The Accounting Review 80 (March). pp 137-166.Harahap, Sofyan Syafri. (2011), Analisa Kritis atas Laporan Keuangan, Edisi ke-5. Jakarta: Raja Grafindo Persada.Harnanto. (2011). Akuntansi Perpajakan. Yogyakarta: BPFE-YogyakartaHarnanto. (2013). Perencanaan Pajak, Edisi Pertama. Yogyakarta: BPFE, YogyakartaIkatan Akuntan Indonesia. Pernyataan Standar Akuntansi Keuangan Nomor 46: Akuntansi Pajak Penghasilan. Jakarta : Salemba Empat, 2002.Islahuzzaman. (2012). Istilah-istilah Akuntansi dan Auditing. Edisi Kesatu. Jakarta: PT. Bumi Aksara.Kayo, Edison Sutan. 2019. Perusahaan Pertambangan di Indonesia. https://www.sahamok.com/perusahaan-pertambangan-di-indonesia/. (12 Mei 2019).Kencana, Maulandy Rizky Bayu. 2019. 3 Sektor Usaha Ini Beri Kontribusi Besar buat Penerimaan Pajak. https://www.liputan6.com/bisnis/read/3247396 /3-sektor-usaha-ini-beri-kontribusi-besar-buat-penerimaan-pajak. (23 Juli 2019)Kiswanto. (2009). â€œDeferred Tax Expense and Accruals Dalam Memprediksi Earning Management: Penelitian Empiris Pada Perusahaan Manufaktur di Bursa Efek Indonesiaâ€. Departemen Ekonomi Universitas Negeri Semarang.Pindiharti,Dewi (2011), Pengaruh Aktiva Pajak Tangguhan,Beban Pajak Tangguhan dan Akrual Terhadap Earning Management.Skripsi,Jakarta : Program S1 Fakultas Ekonomi Dan Bisnis Universitas Islam Negeri Syarif Hidayatullah.Saepulloh, Rahmat. Kontribusi Industri Tambang bagi Pendapatan Negara Capai Rp46,6 Triliun. ttps://www.wartaekonomi.co.id/read212192/kontribusi-industri-tambang-bagi-pendapatan-negara-capai-rp466-triliun.html. (23 Juli 2019)Scott, William R, (2009). Financial Accounting Theory. Fifth Edition. Canada Prentice Hall.Sloan, R. G. (1996). Do Stock Prices Fully Reflect Information in Accruals and Cash Flows About Future Earnings. The Accounting Review Vol 71 No 3Shinta, Yohanes, Haqi. (2019). Pengaruh Beban Pajak Tangguhan Dan Akrual Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2017. Bogor: Program Studi Akuntansi Fakultas Ekonomi Universitas PakuanSuandy, Erly. (2008). Perencanaan Pajak. Jakarta : Salemba Empat.Sugiyono. (2011). Metode Penelitian Kuantitatif Kualitatif dan R&D (12th ed). Bandung: Alfabeta.Sugiyono. (2017). Metode Penelitian Kuantitatif dan Kualitatif &RND. Bandung: Alfabeta.Suhayati, Ely dan Sri Dewi Anggadini, (2009), Akuntansi Keuangan, Edisi Pertama, Yogyakarta:Graha Ilmu.Sulistyanto, Sri. (2007). Manajemen Laba. Jakarta : Grasindo.Sulistyanto, Sri. (2008).Manajemen Laba: Teori dan Model Empiris. Jakarta: PT. Gramedia Widiasarana.Sumomba, Christina Ranty dan Hutomo, Sigit. (2012). Pengaruh Beban PajakÂ Â Â  Tangguhan dan Perencanaan Pajak Terhadap Manajemen Laba. Kinerja, Volume 16, No. 2, Hal. 103-115.Supriyanto,Edy. (2011), Akuntansi Perpajakan, Yogyakarta : Graha Ilmu.Waluyo. (2012). Akuntansi Pajak, Edisi 4. Jakarta: Salemba Empat.Wijayanti. (2006). Analisis Pengaruh Perbedaan Antara Laba Akuntansi dan Laba Fiskal Terhadap Persistensi Laba, Akrual, dan Kas. Makalah Simposium Nasional Akuntansi IX.Wolk, et.al. (2004). Accounting Theory: Conceptual Issues in a Political and Economic Environment. Thomson South-Western.Yulianti. (2004). Kemampuan Beban Pajak Tangguhan dalam Memprediksi manajemen Laba. Simposium Nasional Akuntansi VII. IAIYulianti. (2005). Kemampuan Beban Pajak Tangguhan Dalam Memprediksi Manajemen Laba. Kumpulan Materi Simposium Nasional Akuntansi Vol. VII. Page : 1147-1163.Zain, Mohammad. (2007). Manajemen Perpajakan.Jakarta: Salemba Empat